Close to Transplant Renal Artery Stenosis and Percutaneous Transluminal Treatment - Leonardou Polytimi; Gioldasi Sofia; Pappas Paris (Journal of Transplantation)
Purpose. To evaluate the efficacy of percutaneous transluminal angioplasty (PTA) in the management of arterial stenosis located close to the allograft anastomosis (close-TRAS). Materials and Methods. 31 patients with renal transplants were admitted to our institution because of persistent hypertension and impairment of transplant renal function and underwent angiography for vascular investigation. 27 were diagnosed suffering from transplant renal artery stenosis (TRAS), whereas 4 had severe iliac artery stenosis proximal to the transplant anastomosis (Prox-TRAS). 3 cases of TRAS coexisted with segmental renal arterial stenosis, whereas 3 other cases of TRAS were caused by kinking and focal stenosis in the middle of the transplanted renal artery. Results. Angioplasty and stenting were successfully applied to all patients with iliac artery stenosis as well as to those with TRAS and segmental artery stenosis. Two of three patients with kinking were well treated with angioplasty and stenting, whereas one treated only with angioplasty necessitated surgery. No major procedure-related complications appeared, and the result was decrease of the serum creatinine level and of the blood pressure. Conclusions. PTA is the appropriate initial treatment of TRAS and close-TRAS, with low morbidity and mortality rates, achieving improvement of graft function and amelioration of hypertension.